Understanding Reproductive Aging in Wildlife to Improve Animal Conservation and Human Reproductive Health - Comizzoli, Pierre; Ottinger, Mary Ann (Frontiers in Cell and Developmental Biology, 2021)
Similar to humans and laboratory animals, reproductive aging is observed in wild species - from small invertebrates to large mammals. Aging issues are also prevalent in rare and endangered species under human care as their life expectancy is longer than in the wild. The objectives of this review are to (1) present conserved as well as distinctive traits of reproductive aging in different wild animal species (2) highlight the value of comparative studies to address aging issues in conservation breeding as well as in human reproductive medicine, and (3) suggest next steps forward in research. From social insects to mega-vertebrates, reproductive aging studies, or observations in the wild and in breeding centers are often at the physiological or organismal scale (senescence) rather than at the germ cell level. Overall, multiple traits are conserved across very different species (depletion of the ovarian reserve or no decline in testicular functions), but unique features also exist (endless reproductive life or unaltered quality of germ cells). There is a broad consensus about the need to fill research gaps because many cellular and molecular processes observed during reproductive aging remain unknown. More research in male aging is also needed across all species. Furthermore, studies on reproductive aging of target species in their natural habitat (sentinel species) are crucial to define more accurate reproductive indicators relevant to other species, including humans, sharing the same habitats. Wild species can significantly contribute to our general knowledge of a crucial phenomenon and provide new approaches to extend reproductive lifespan.